Математическое моделирование образования отложения на поверхности теплопередачи пластинчатого теплообменника - Мацегора, Александр Иванович (Национальный технический университет "Харьковский политехнический институт", 2017)
Представлена математична модель пластинчатого теплообмінника (ПТО) з забрудненням на поверхні теплообміну. Модель враховує зміну параметрів процесу вздовж довжини каналу і в часі з розвитком слою забруднень. Параметри моделі були ідентифіковані з використанням даних моніторингу теплових характеристик ПТО, працюючих в промисловості і комунальному теплозабезпеченні. Модель може бути використана для моделювання теплових характеристик ПТО, працюючих з конкретним теплоносієм, та для аналізу впливу на теплові характеристики ПТО геометрії гофрування пластин, температурної програми і швидкості потоку в каналах.

The mathematical model of plate heat exchanger (PHE) with fouling deposition on heat transfer surface is presented. The model is accounting for the change of process parameters along the channels length and in time with the development of fouling deposition layer. The model’s parameters were identified using data of monitoring the thermal performance of PHEs operating in industry and District Heating. The model can be used to simulate thermal performance of PHEs working with specific media and to analyze the influence of plate’s corrugation geometry, temperature program and flow velocity in channels on PHE thermal performance in conditions of fouling.
The mathematical modelling of fouling formation along PHE heat transfer surface
Keywords: загрязнения; теплообменные потоки; осаждаемое вещество; термическое сопротивление